Vehicle sideslip estimation: A kinematic based approach. (October 2017) - Selmanaj, Donald; Corno, Matteo; Panzani, Giulio; Savaresi, Sergio M.
Abstract: This paper deals with vehicle sideslip angle estimation. The paper introduces an industrially amenable kinematic-based approach that does not need tire–road friction parameters or other dynamical properties of the vehicle. The convergence of the estimate is improved by the introduction of a heuristic based on readily available inertial measurements. The method is tested on a vast collection of tests performed in different conditions, showing a satisfactory behavior despite not using any information on the road friction. The extensive experimental validation confirms that the estimate is robust to a wide range of driving scenarios.